Evaluación del efecto de distintos programas de luz, para aves ponedoras de la raza (rhode island), en la ciudad de Loja - Cueva Rueda, Byron Danilo (2015)
This research envelope, "evaluation of the effect of various programs of light, poultry hens of race (Rhode Island) in the city of LOJA" was objectives:  Analyzer the responses of birds to the duration of the long photoperiod of natural light with artificial light, in one of the groups experimental.  Determiners the increase in weight, feed intake and feed in each of the groups conversion experimental.  Establish profitability each of the lighting programs applied to laying hens. Research yourselves two experimental groups "A" and "B" by entering a hundred birds of position (baby) of the Rhode Island race, for each group, to receive different treatments. Treatment for the group "A" consisted of administering a daily program of lighting, only with natural light from breeding, lift and position of the birds in experiment. I.e. they received around 11 to 12 hours a day of daylight (one day). At the moment that ended the day around 18 H 00 pm, just the day for birds, curtains down and the shed was closed. Treatment for the group "b" Consisted to apply a daily program of lighting, combined between daylight and artificial light, i.e. when it ended the day around 18 H 00 pm and the natural light is off, is down the barn curtains and lighting the lights to lengthen the day birds in experiment. Applied 14 hours a day of light combined to breed and raise (up to week 15 of the bird life) and for the prepostura and position applied for 15 hours per day of this combined light. The investigation lasted for 22 weeks and their variables were: feed intake, increased weekly weight, feed conversion, the program of light effect (age of sexual maturity of the bird at the time of commissioning and percentage of egg hen/day production), mortality and profitability. Arriving to determine how, the best effect of the different programs of light is designated, the experimental group "B" in all their study variables. The increased consumption of food obtained it the treatment of group "B" with an average of 7.28 Kg of food consumed. Likewise shown a better average increase of weight for the treatment of the experimental group "B" of 1.10 Kg/bird, while the treatment of group "A" reached an average weight of 1 Kg bird. Better feed conversion was awarded by the treatment of the "A" group of 6.34: 1 considerably in response to a good feed conversion between applied photoperiod, consumed food and animal product higher average egg production is designated, the experimental group "B" since their effects are reflected, in the prompt you mature sexually Ave at the time of commissioning giving greater variety of eggs with 37% while the group "A" reached 24%. The highest percentage of mortality is evidence in the experimental group 'A' with a 6% while the group "B" only obtained 3%, thus looking like best treatment reduced mortality group. Higher profitability appears for the "B" group that just in four weeks of commissioning of the birds reached an 11.67% meanwhile, in the group "A" there are no profitability, barely reached the 1.57%. This way is recommended, that the administration of a program of laying hens of race (Rhode Island) light is much more expensive, being is directly proportional to the increase in the percentage of egg production, which means that it is profitable for the poultry producer.